Pengaruh Penggunaan Media Flash Card terhadap Keterampilan Membaca Permulaan pada Siswa Kelas II di SD IT Ummu Fathima Kota Bengkulu - Heru Frayetno; Bobi Endiko Saputra; Yosi Yoliza; Andre Taulani (MODELING: Jurnal Program Studi PGMI, 2026)
This study aims to determine the effect of using flashcards on the early reading skills of second-grade students at SD IT Ummu Fathima, Bengkulu City. The study employs a quantitative approach using a quasi-experimental design—specifically, a non-equivalent control group design. The study population consisted of all students at SD IT Ummu Fathima, Bengkulu City, while the sample comprised 40 students: 20 from class IIA (experimental group) and 20 from class IIB (control group). Data collection techniques included observation, testing, and documentation. Data analysis was conducted using normality tests, homogeneity tests, and hypothesis testing (Independent Sample t-test) with the aid of IBM SPSS Statistics Version 25. The results indicate that the implementation of instruction using flashcards improved with each session, ranging from "good" to "very good." The mean post-test score for the experimental group was 73.25, which was higher than that of the control group (68.00). Hypothesis testing yielded a significance value of 0.003 (p < 0.05); thus, the null hypothesis (H?) was rejected, and the alternative hypothesis (H?) was accepted. Consequently, it can be concluded that the use of flashcards has a significant effect on the early reading skills of second-grade students at SD IT Ummu Fathima, Bengkulu City. Flashcards proved effective in increasing learning interest, facilitating letter and word recognition, and helping to improve early reading skills.